Expansão urbana do município de São Miguel do Oeste - SC, num contexto social, geomorfológico e arquitetônico - Maziero, Celí (2018)
Cities are complex and dynamic bodies whose spatial configuration varies according to several factors, such as socioeconomic influence, availability of resources and geomorphology. The high pressure for space, associated with an unfavorable geomorphological condition, induces disordered growth, exposing human beings to risk and reducing their quality of life. Thus, this work aims at analyzing the process of urban expansion of the city of São Miguel do Oeste – SC, based on geomorphological, temporal, spatial and architectural aspects, with the purpose of contributing to the understanding of the relation man/space/time. The relief analysis was performed by Digital Elevation Model (DEM), generating maps of slope, hypsometric and topographic profiles. The analysis of the urban expansion was carried out through documents and historical maps of the collection of the Municipality. The study of temporal transformations of constructive techniques and architectural styles was conducted through documents and photographic records of typical buildings from each historical period. The formation of the city of São Miguel do Oeste occurred in a flat relief area, near the headwaters of the Guamirim River and its expansion was conditioned by the erosive escarpments observed on the East and West edges, where the slope reached 47%. Its preferential axis of development followed North and South directions, towards the smoothest relief and with the main routes of entry and exit of the city. The beginning of the city dates back to the 1950s and, in its constructions, the strong influence of European thought is evident, with wood being the main raw material. The period of greatest urban expansion was observed in the 1970s, induced by rural exodus and especially by migratory processes originating in other states. This context is marked by new forms and techniques of construction using concrete and glass, highlighted in Modernist architecture. The 1980s are characterized as a period of intense urbanization, marked by the emergence of the Brutalist style. In the 1990s, Postmodernist works appeared and in the 2000s, the Neoclassical buildings, both highlighting the use of glass structures with tendencies to their own identities. As of 2010, there is a clear concern about the functionality of buildings and the well-being of their users, in which steel and glass are highlighted. The city of São Miguel do Oeste began its history at the headwaters of the Guamirim River and its current configuration was conditioned by the steep relief of its surroundings. Throughout the development process, the city has adapted to available resources and architectural trends, clearly demonstrating the substitution of wood as the basic raw material for the use of concrete, steel and glass.